The Role of Marketing Agencies in Eggs Selling at Layer Farmers in Indonesia: A Case Study in West Java, Bali and South Sulawesi - V. S. Lestari; . Saadah; H. M. Ali; A. Natsir (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
The aim of this study was to determine the role of some marketing agencies in selling eggs of layer farmers in Indonesia. The research was conducted in West Java, Bali and South Sulawesi. The selection of those regions was based on the category that they had the most populous layer farmers compared to other regions. The number of respondents was determined using quota sampling method from FAO poultry industry data, i.e. 60 layer farmers of West Java and South Sulawesi respectively, and 41 farmers of Bali. The farmers involved in the study were those having layer population between 2000-5000 hens. Data were collected from the respondents through deep interview using a questioner that have been prepared before hand and conducted in May 2010. The results of the study indicated that among the marketing agencies studied in the three regions; West Java, Bali and South Sulawesi, the role of whole sellers in eggs selling of layer farmers was the most important one, followed by restaurants, traditional markets, consumers and the poultry shop, respectively. In terms of egg selling price in the three regions, the most expensive was in Bali and the cheapest one was in South Sulawesi.